تفعيل مبدأ المساواة وسبل تطبيقه في المرفق العام الإلكتروني - جروني، فائزة; قده، حنان (جامعة صفاقس - كلية الحقوق, 2021)
إن تسارع وتيرة التغيرات والتطورات التي يشهدها العالم اليوم، خاصة في ظل ما يعرف بالمرفق العام الإلكتروني، وما لذلك من ارتباط وثيق بتطبيق تكنولوجيا المعلومات والاتصال في المرافق العامة الإدارية، بهدف أداء الخدمات الحكومية بسرعة وفاعلية مما يؤدي إلى تحقيق الشفافية، والمساواة، يساهم ولو جزئيا في القضاء على البيروقراطية، وبذلك تساهم الخدمات التكنولوجية بشكل كبير في تحسين علاقة الإدارة بالمواطن. وتخضع المرافق العامة على اختلاف أنواعها وتصنيفاتها لمجموعة من المبادئ العامة الموحدة اللازمة لإنجاز مهامها في تحقيق الصالح العام على أفضل وجه، ومن بين هذه المبادئ مبدأ مساواة الأفراد في الاستفادة من خدمات المرفق العام، إلا أن إدارة المرافق العامة بالنظام الإلكتروني بدلا من إدارتها بالطريقة التقليدية ينبغي أن يتزامن مع تفعيل مبدأ المساواة والعمل على تطبيقه من أجل التوافق مع النظام الإلكتروني." The rapid pace of changes and developments in the world today, especially in the context of the so-called e-public facility, and its close linkage with the application of information and communication technologies in the administrative public facilities, with a view to the speedy and effective performance of government services leading to transparency, Equality, and even partly contributes to the elimination of bureaucracy, and thus the technological services contribute significantly to improving the management relationship with the citizen. Public utilities of different types and classifications are subjected to a set of common general principles that are necessary to accomplish their functions in the best interests of the public, including the principle of equal access to public utility services, but the management of public utilities in the electronic system, instead of being managed in the traditional way, it should coincide with the operationalization of the principle of equality and work on its application in order to conform to the electronic system."
Keywords: المرافق العامة -- المرافق الإلكترونية -- الأنظمة الإلكترونية